Korupsi dalam Perspektif Budaya Hukum - Muhammad Syamsudin (Unisia, 2007)
In the perspective of legal culture corruption denotes a behavior that contradicts to values and norms either those of honesty, social, religion or the law. But, the emerging of the corruption itself is influenced by individual and collective need and demand, and also iit is supported by social culture environment that inherited the corruption tradition. Besides, legal culture of the government dose not justify law and pays priority over social status, economy, and that of politics of corruptor. The internal legal cultutre of law enforcement itself does not support to solve the corruption that shows the corruption in the process of court. Departing from this phenomenon it is clearly that corruption is regarded as society culture that difficult to solve, instead the corruption can be proved legally but it can be regarded as other meaning for instance commission, kompensation, reward, insentive, return fee and so on. Kaywords: Corruption, Law En- forcement, Legal Culture